Child development : a practical introduction - Crowley, Kevin (Psychologist) (London : Sage, 2014)
Covering all the main areas of study and assuming no prior knowledge of the topic, this book takes the reader through the key elements of child development. Drawing on research, and referencing key theories in the field, it provides students with a comprehensive overview of the subject and its application to early years practice. Topics explored include: * The development of language and literacy * Cognition and memory * Social and emotional development * Physical development (including reference to Development Matters and the EYFS age two progress check) * Child development and the early years curriculum * Researching child development Learning features that help to make the text accessible include: chapter overviews; questions for discussion; suggestions for further reading and an end of chapter glossary.
9. Language and literacy. The development of language -- The course of language development : Developments in infancy ; First words -- First sentences -- Development of pragmatic skills -- Theories of language development : Learning theory ; Nativist theory ; Interactionist views -- Other topics in language development : Learning disabilities and language development ; Sign language acquisition ; Bilingual language development ; Specific language impairment -- The development of literacy : The course of reading development ; Ehri's phase theory ; Phonological awareness and reading development -- Other topics in literacy development : The development of spelling ; Developmental dyslexia -- Supporting language and literacy development -- 10. The role of play. Types of play -- Defining play -- Theories of play -- Play and development -- Play as an educational tool -- Play therapy -- 11. The role of the adult. Child development theories and the role of the adult -- The role of the parent -- Styles of parenting -- Parenting styles and developmental outcomes -- The role of the early years practitioner -- Adult-child interactions -- Adult-child interactions in the context of play.
Includes bibliographical references and index.
Keywords: Child development; Child care